Aphid Colonization Affects Potato Root Exudate Composition and the Hatching of a Soil Borne Pathogen - Hoysted, Grace A.; Bell, Christopher A.; Lilley, Catherine J.; Urwin, Peter E. (Frontiers in Plant Science, 2018)
Abstract Plants suffer multiple, simultaneous biotic threats from both above and below ground. These pests and/or pathogens are commonly studied on an individual basis and the effects of above-ground pests on below-ground pathogens are poorly-defined. Root exudates from potato plants (Solanum tuberosum L.) were analysed to characterise the top-down plant-mediated interactions between a phloem-sucking herbivore (Myzus persicae) and a sedentary, endoparasitic nematode (Globodera pallida). Increasing inocula of the aphid, M. persicae, reduced the root mass of potato plants. Exudates collected from these roots induced significantly lower hatching of second-stage juveniles from G. pallida eggs over a 28-day period, than those from uninfested control plants. Inhibition of hatch was significantly positively correlated with size of aphid inoculum. Diminished hatching was partially recovered after treatment with root exudate from uninfested potato plants indicating that the effect on hatching is reversible but cannot be fully recovered. Glucose and fructose content was reduced in root exudates from aphid-infested potato plants compared to controls and these sugars were found to induce hatching of G. pallida, but not to the same degree as potato root exudate. Supplementing aphid-infested potato root exudate with sugars did not recover the hatching potential of the treatment, suggesting that additional compounds play an important role in egg hatch. The first gene up-regulated in the closely related potato cyst nematode G. rostochiensis post-exposure to host root exudate, Neprilysin-1, was confirmed to be up-regulated in G. pallida cysts after exposure to potato root exudate and was also up-regulated by the sugar treatments. Significantly reduced up-regulation of Gpa-nep-1 was observed in cysts treated with root exudates from potato plants infested with greater numbers of aphids. Our data suggest that aphid infestation of potato plants affects the composition of root exudates, with consequential effects on the hatching and gene expression of G. pallida eggs. This work shows that an above-ground pest can indirectly impact the rhizosphere and reveals secondary effects for control of an economically important below-ground pathogen.